Virtualized 5G Tesbed using OpenAirInterface: Tutorial and Benchmarking Tests - Dória, Matheus; Sousa, Vicente; Campos, Antonio; Oliveira, Nelson; Eduardo, Paulo; Filho, Paulo; Lima, Carlos; Guilherme, João; Luna, Daniel; Rego, Iago; Fernandes, Marcelo; Neto, Augusto (Journal of Internet Services and Applications, 2024)
The development of 5G and its evolutionary path to 6G brings virtualization as close as possible to the antennas. Native 3GPP systems are now software running at servers boosted by accelerator cards to cope with computationally intense signal processing. Meanwhile, the Radio Frequency (RF) front-end is still proprietary hardware, sheltering specific PHY-layer procedures like passband amplification/modulation. This approach takes advantage of the software’s flexibility while keeping the complex microsecond signal processing performance from modern telecommunication systems. This paper provides tutorial material on the Core Network and Radio Access Network of OpenAirInterface (OAI) 5G stack on top of Universal Software Radio Peripheral (USRP) platforms. A set of blueprints showcases OAI’s ability to provide a virtualized 5G network with different transmission capabilities and the possibility to use it with commercial mobile phones. Configuration discussions and throughput benchmark analyses follow installation and deployment instructions. Our results show that 5G prototyping using OAI and USRP frontends can lead to good reproducibility and consistent throughput.